The policy, structure and evaluation of long-term care networks: the differentiated requirements referred to the example of integrated long-term care in Austria. (13th March 2009) - Ostermann, Herwig; Staudinger, Bettina; Staudinger, Oskar; Kern, Katharina; Them, Christa; Staudinger, Roland
Long-term care facilities are currently exposed to powerful forces demanding organisational change based on synergy and cooperation. The adoption of network structures is frequently regarded as an appropriate solution to this challenge by health politics. Focusing on the concrete example of the integrated long-term care network for the elderly in the Austrian land of Tyrol, the article aims (1) to explore which criteria the lawgiver formulated for the nursing cooperation structures, (2) to examine which targets and functional requirements the managers of the nursing institutions involved theoretically demand from a network structure in long-term care and (3) to investigate the functionality of the network by means of an empirical study focusing on the processes at interorganisational interfaces. Merging the major findings of the legal, theoretical and empirical enquiry, structural and functional efficiency criteria are derived, which are suggested as a framework for the evaluation of integrative nursing networks.